A randomized trial of primary intensive care to reduce hospital admissions in patients with high utilization of inpatient services. - Sledge, William H; Brown, Karen E; Levine, Jeffrey M; Fiellin, David A; Chawarski, Marek; White, William D; O'Connor, Patrick G (Disease management : DM, 2006)
Randomized controlled trials of case management in primary care have been infrequent and contradictory. The aim of this study was to determine if a clinic-based ambulatory case management intervention, Primary Intensive Care (PIC), would reduce hospital utilization and total cost and/or improve health outcomes among primary care patients with a recent history of high use of inpatient services. Current patients with > or =2 hospital admissions per year in the 12-18 months prior to recruitment in an urban primary care clinic were enrolled in a randomized clinical trial. Patients were randomized to the PIC intervention or usual care. PIC patients underwent a comprehensive multidisciplinary assessment with the result being a team-generated plan. The PIC team nurse practitioner served as case manager for the 12 months of follow-up and provided services designed to implement the care plan for those in the experimental group. Health care use, function, and a medication adherence scale were measured at baseline and at 12 months. There were no significant differences when either comparing the number of admissions pre and post enrollment within groups or the followup results post intervention between groups. A similar result was noted for the number of emergency department visits. The number of clinic visits increased in the intervention group by 1.5 visits per year which was statistically significant when compared to the control group. Overall functional status, health outcomes, and the Mental Health Functional Status subscore did not change significantly in either group during the study. We were unable to detect a difference in hospital use or functional status, mental health function, or medication adherence among patients who require frequent hospital admissions using our intervention.
Keywords: Adult; Aged; Aged, 80 and over; Delivery of Health Care; Female; Follow-Up Studies; Hospitalization; Humans; Intensive Care; Male; Middle Aged; Primary Health Care